2011
DOI: 10.4269/ajtmh.2011.10-0668
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Decrease in Malaria Transmission after Large-Scale Indoor Residual Spraying with Bendiocarb in Benin, an Area of High Resistance of Anopheles gambiae to Pyrethroids

Abstract: In 2008, the National Malaria Control Program in Benin implemented a vector control intervention based on indoor residual spraying (IRS). Four districts of high resistance of Anopheles gambiae to pyrethroids were sprayed with bendiocarb. More than 350,000 inhabitants have been protected. Entomologic parameters in the control area were compared with those in intervention sites. The study has shown a drastic decrease in the An. gambiae biting rate in the sprayed areas. Results of an enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 22 publications
5
72
2
Order By: Relevance
“…Following the massive increase in PYR insecticide resistance in African populations of An . gambiae , several African countries have tried to preserve the efficacy of vector control by switching from PYRs to CXs or OPs, in accordance with the American President’s Malaria Initiative [60], in collaboration with the National Malaria Control Program [61]. However, duplicated ace-1 resistance alleles are already widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Following the massive increase in PYR insecticide resistance in African populations of An . gambiae , several African countries have tried to preserve the efficacy of vector control by switching from PYRs to CXs or OPs, in accordance with the American President’s Malaria Initiative [60], in collaboration with the National Malaria Control Program [61]. However, duplicated ace-1 resistance alleles are already widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the beneficial effects of IRS in malaria prevention have been reported in both high and low malaria endemic areas [1–7]. IRS contributed to the elimination or dramatic reduction of malaria in various parts of Latin America, Asia, and Europe [8].…”
Section: Introductionmentioning
confidence: 99%
“…A different observational study in the same country showed that carbamates and organophosphates were more effective compared to using DDT [45]. Additional empirical evidence from Benin also showed a high efficacy of bendiocarb [49]. On the contrary, there has been some evidence on the resistance of An.…”
Section: Discussionmentioning
confidence: 99%